ТО THE QUESTION OF ILLUMINATION OF PROBLEM OF FORMING OF PROFESSIONAL ABILITY OF FUTURE TEACHER OF FINE ART TO THE ARTISTIC TEACHING OF SCHOOLBOYS (Pedagogy of Higher and Secondary Education, 2022)
The basic rules (situations) of an experimental research of process of formation of professional ability of the future teacher of fine arts to art training of the schoolboys in conditions of system of art - pedagogical education are considered (examined).